PENDUGAAN CADANGAN KARBON ABOVE GROUND BIOMASS DI KECAMATAN LUMBAN JULU KABUPATEN TOBA SAMOSIR - Desrina Natalia Manalu; Rahmawaty Rahmawaty; Riswan Riswan (Peronema Forestry Science Journal, 2016)
The destruction of forests, climate change and global warming, causing indirect benefits from the forest is reduced, because the forest is the largest carbon sink and play an important role in the global carbon cycle. In order to reduce the rate of global warming, this study estimated the potential of carbon stock. The study aimed to calculate carbon stocks above ground biomass in Lumban Julu Sub-District. This study was conducted in February to May 2015 in Lumban Julu Sub-District, Toba Samosir District. Non destructive method were used in this study. Parameters measured in the field were diameter breast height (DBH) and height of the tree.The result showed that the amount of carbon content in above ground biomass in Lumban Julu Sub-District stands in Jangga Toruan Village and Jangga Dolok Village, respectively by 202,59 ton/ha and 204,79 ton/ha. The value of the carbon content in Lumban Julu Sub-District classified as good. Keywords: Above ground biomass, carbon cycle, global warming, Lumban Julu, Toba Samosir